Chemical heterogeneity of the Emeishan mantle plume: Evidence from highly siderophile element abundances in picrites - Li, J.; Wang, Xuan-Ce; Ren, Z.; Xu, J.; He, B.; Xu, Y. (Pergamon-Elsevier Science Ltd, 2013)
Highly magnesian lavas or picrites have the potential to preserve important information about the origin and thermochemical state of the mantle source(s) of large igneous provinces. We have conducted a comprehensive study of highly siderophile element (HSE) concentrations in picrites from the ca. 260 Ma Emeishan large igneous province. We show that HSE abundances in the Emeishan picrites are greater than those in mid-ocean ridge basalts (MORBs) and parental melts of Hawaiian picrites, but are similar to those in komatiites. The picrites have two types of C1-normalized HSE patterns: (a) type 1, as represented by the Muli picrites is similar to that of the primitive upper mantle; (b) type 2, as represented by the Dali picrites resembles East Greenland and Iceland picrites. Pt/Ir and Pd/Ir ratios in the type 2 picrites are higher than those in type 1 picrites. The primary melt compositions of the studied samples have been estimated by back-addition of equilibrium olivine. The calculated HSE abundances of the parental liquids of the Dali and Muli picrites are higher than those of the parental melts to Hawaiian picrites. Along with previously published isotopic data, our study provides further evidence for chemical heterogeneity of the Emeishan mantle plume.